STUDENTS' MATHEMATICAL REPRESENTATION AND REASONING SKILLS THROUGH AN ETHNOMATHEMATICS-BASED RME APPROACH - Matital, Luis; Ratumanan, Tanwey G; Laamena, Christina M (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
This study was conducted to obtain an overview of the differences between ethnomathematics-based and conventional RME models on students' mathematical representation and reasoning abilities on curved-sided space building material. Researchers used quantitative research methods. This research is aquasi experiment with pretest postest research design conducted on grade IX students of SMP Negeri 1 Seram Barat. The samples of this study were students of class IX A. and IX E, consisting of 29 students for each class, which were taken by non-random sampling or purposive sampling. The experimental class used the ethnomathematics-based RME learning model while the control class used the conventional learning model. The research data were obtained through written tests in the experimental and control classes. The normality test showed that the data in both groups were normally distributed. The data homogeneity test also shows that the data in both groups are homogeneous. The results of the independent t-test showed that there was a difference in the average representation and reasoning skills of the experimental class as well as the control class, with a sig value of 0.00 <0.05. The N-gain test shows the effectiveness of the learning provided. The experimental class with representation ability has an average N-gain of 0.08 (high category) > 0.45 (medium category) for the control class. In the reasoning ability of the experimental class with an average of 0.83 (high category) > 0.28 (low category) for the control class